Improving Students’ Questioning Achievement Through Picture Word Inductive Model ( PWIM ) - Indah Sari Ayu Nasution and Sri Minda Murni (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study deals with improving students’ questioning achievement through picture word inductive model. The subject of the research was class X SMA Amir Hamzah Medan consisted of 22 students. This study was conducted by using classroom action research. The instruments for collecting data were oral test for quantitative data and diary notes, interview, observation list, and questionnaire sheet for qualitative data. The result of the research showed that the mean of the students’ scores in the second cycle (80.63) was higher than in the first cycle (70.36). Based on the qualitative data, the students studies more enthusiastically during teaching learning process in the second cycle. It can be concluded that picture word inductive model could improve students’ questioning achievement.